Trump says U.S. will have ‘direct’ talks with Iran (WP Company LLC d/b/a The Washington Post, 2025)
President Donald Trump said April 7 that Iran and the United States have begun ‘direct’ talks over Tehran’s nuclear program, contradicting Iranian leaders’ rejection of the idea just hours before.